2022
DOI: 10.1111/apm.13232
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PCR‐based syndromic testing compared to bacterial culture in patients with suspected pneumonia applying microscopy for quality assessment

Abstract: Performance of PCR-based syndromic testing compared to bacterial culture in patients with suspected pneumonia applying microscopy for quality assessment. APMIS. 20222022; 130: 417-426. Syndromic testing for lower respiratory tract infections with BioFireÒ FilmArrayÒ Pneumonia Panel Plus (BF) detects 27 pathogens with a turn-around-time of one hour. We compared the performance of BF with culture. Samples from 298 hospitalized patients with suspected pneumonia routinely sent for culture were also analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The authors plan a follow-up randomized controlled trial to assess the impact of syndromic PCR on antibiotics prescribing for CAP [25]. However, Andrews et al [26] found, in a prospective analysis of 322 specimens from adults suspected of pneumonia, that the multiplex PCR panel had a 70% sensitivity and 43% specificity for CAP. Low specificity represents detection of pathogens in patient specimens who did not have clinical pneumonia, and 53 out of 129 (41%) patients who did not have clinical pneumonia received antibiotics, indicating that test ordering is a potential target for diagnostic stewardship [26].…”
mentioning
confidence: 99%
“…The authors plan a follow-up randomized controlled trial to assess the impact of syndromic PCR on antibiotics prescribing for CAP [25]. However, Andrews et al [26] found, in a prospective analysis of 322 specimens from adults suspected of pneumonia, that the multiplex PCR panel had a 70% sensitivity and 43% specificity for CAP. Low specificity represents detection of pathogens in patient specimens who did not have clinical pneumonia, and 53 out of 129 (41%) patients who did not have clinical pneumonia received antibiotics, indicating that test ordering is a potential target for diagnostic stewardship [26].…”
mentioning
confidence: 99%